Associations of Fibrinogen, Factor VII and PAI-1 with Baseline Findings among 10,500 Male Participants in a Prospective Study of Myocardial Infarction - Scarabin, Pierre-Yves; Aillaud, Marie-Francoise; Amouyel, Philippe; Evans, Alun; Luc, Gérald; Ferrières, Jean; Arveiler, Dominique; Juhan-Vague, Irène (Thrombosis and Haemostasis, 1998)
The contribution of coagulation factors and fibrinolytic variables to the development of ischaemic arterial disease is still not clearly established. The PRIME study is a prospective cohort study of myocardial infarction in men aged 50-59 years and recruited from three MONICA field centers in France (Lille, Strasbourg and Toulouse) and the center in Northern Ireland (Belfast). Baseline examination included measurement of plasma fibrinogen, factor VII, and PAI-1 activity in over 10,500 participants. We investigated the associations of these haemo-static variables with cardiovascular risk factors, prevalent atherosclerotic disease and geographical area. Fibrinogen level increased with age, smoking, waist-to-hip ratio, LDL-cholesterol, and it decreased with educational level, leisure physical activity, alcohol intake and HDL-cholesterol. Factor VII activity increased with body mass index, waist-to-hip ratio, triglycerides, HDL- and LDL-cholesterol. PAI-1 activity increased with body mass index, waist-to-hip ratio, triglycerides, alcohol intake, smoking, and decreased with leisure physical activity. PAI-1 level was higher in diabetic subjects than in subjects without diabetes. Cardiovascular risk factors explained 8%, 9%, and 26% of the total variance in fibrinogen, factor VII, and PAI-1, respectively. Compared with participants without prevalent cardiovascular disease, those with previous myocardial infarction (n = 280), angina pectoris (n = 230), or peripheral vascular disease (n = 19) had significantly higher levels of fibrinogen, but those with stroke (n = 67) had not. PAI-1 activity showed a similar pattern of association. The odds ratio for cardiovascular disease associated with a rise of a one standard deviation in fibrinogen and PAI-1 was 1.31 (95% confidence interval: 1.20 to 1.42, p <0.001) and 1.38 (95% confidence interval: 1.27 to 1.49, p <0.001), respectively. After adjustment for cardiovascular risk factors, these associations were attenuated but remained highly significant. There was no significant association between factor VII activity and prevalent cardiovascular disease. Fibrinogen level and, to a lesser extent, factor VII and PAI-1 activity were higher in Northern Ireland than France after adjustment for the main cardiovascular risk factors. These geographical variations are consistent with the 2 to 3-fold higher incidence of myocardial infarction in Northern Ireland than France. Our results provide further epidemiological evidence for a possible role of fibrinogen and PAI-1 in the pathogenesis of coronary heart disease.